The Resonant Roots of Pappaseng: Seeking Musical Inspiration from the Film Kuru Sumange - Aziz, Baso Indra Wijaya; Burhan, Mukhamad Agus; Irwandi, Irwandi; Skinner, Anthea (Institut Seni Indonesia Yogyakarta, 2025)
This article examines the creative process of creating film music inspired by the cultural heritage of the Bugis people, focusing specifically on the incorporation of pappaseng verses in the film Kuru Sumange. Pappaseng denotes the oral transmission of ancestral wisdom, moral guidance, and philosophical insights that have been repeatedly passed down through generations, embodying profound ethical and spiritual values that are intricately woven into Bugis culture. This study emphasizes how film music serves as a medium for revitalizing traditional values, enabling them to be reimagined and expressed through modern artistic e ces amidst the challenges posed by modernization and the diminishing presence of oral traditions. The study utilizes a Practice-Based Research (PBR) method, framing the process of musical creation as a method for gathering data and a way to interpret them analytically. This method intertwines the process of composition with the act of inquiry, transforming the music into a space for generating knowledge. In the case of Kuru Sumange, selected pappaseng quotations are converted into lyrics and further crafted into melodic, harmonic, and rhythmic structures that closely align with the film’s narrative flow and emotional atmosphere. This transformation allows the music to serve not solely as an aesthetic enhancement to the visual imagery, but also as a means of conveying traditional values to contemporary audiences. The findings indicate two key contributions: firstly, film scenes serve as the main stimuli for musical creation, influencing decisions regarding instrumentation, dynamics, and thematic development; secondly, the philosophical dialogues found in pappaseng are skillfully transformed into lyrical content, thus connecting oral tradition with cinematic expression. This work showcases the considerable potential of music as a culturally contextual and emotionally impactful approach for preserving culture, facilitating intergenerational communication, and creatively revitalizing Bugis heritage through local cinema.